2014
DOI: 10.1016/j.vaccine.2014.09.031
|View full text |Cite
|
Sign up to set email alerts
|

The impact of introducing new vaccines on the health system: Case studies from six low- and middle-income countries

Abstract: Although the new vaccine introductions were viewed as intrinsically positive, on the whole there was no evidence that they had any major impact, positive or negative, on the broader health systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 19 publications
0
33
1
Order By: Relevance
“…This factor impacts, in particular, the ability to maintain a vaccine at the appropriate temperature, especially in remote areas with limited infrastructure [21], and there remains a need to develop and implement vaccines stable at ambient temperatures [60,61]. Poor vaccine stock supply may lead to under-provision of a newly-introduced vaccine, especially in the first few months of program delivery, when demand may exceed expectations or when a catch-up strategy has not been incorporated into forecasting predictions [15,62]. This, especially if accompanied by negative media coverage of shortfalls, as occurred in South Africa for a number of different new vaccines in 2009-2010 may affect public confidence in vaccination programs and reduce vaccine uptake [62].…”
Section: Vaccine Supply and Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…This factor impacts, in particular, the ability to maintain a vaccine at the appropriate temperature, especially in remote areas with limited infrastructure [21], and there remains a need to develop and implement vaccines stable at ambient temperatures [60,61]. Poor vaccine stock supply may lead to under-provision of a newly-introduced vaccine, especially in the first few months of program delivery, when demand may exceed expectations or when a catch-up strategy has not been incorporated into forecasting predictions [15,62]. This, especially if accompanied by negative media coverage of shortfalls, as occurred in South Africa for a number of different new vaccines in 2009-2010 may affect public confidence in vaccination programs and reduce vaccine uptake [62].…”
Section: Vaccine Supply and Deliverymentioning
confidence: 99%
“…A range of factors may contribute to lower than desirable levels of vaccine introduction. Decision-making processes, economic and financial aspects of NVIs are critical ones and have been extensively described [10][11][12][13][14][15][16][17][18][19][20]. Besides these aspects, implementation and integration of new vaccines bring additional logistical complexity to delivery of existing immunization programs in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…The pneumococcal conjugate vaccines (PCVs) has been shown to be safe and highly effective in preventing invasive pneumococcal disease (IPD) and reducing the burden of pneumococcal disease in children, both in developed and developing countries [16]. In sub-Saharan Africa, which carries the highest burden of the disease worldwide, many countries have recently introduced PCVs into their childhood vaccination programs [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Of remark, previous studies have shown that despite the fact that introduction of PCV led to a decline in the burden of pneumococcal meningitis caused by those serotypes that are covered by the PCV [1,2,4,5,7], on the other hand, it resulted in relative increase in the burden of pneumococcal meningitis caused by non–PCV serotypes. Thus, serotype-specific pneumococcal surveillance is key to assess and understand the impact of PCV in the epidemiology of pneumococcal meningitis, including to assess the potential replacement of PCV serotypes by non-PCV serotype, following the introduction of PCV [112].…”
Section: Introductionmentioning
confidence: 99%
“…This paper aims to explore the impact of PCV introductions on EPI and health systems in four countries in sub-Saharan Africa. The research was part of a larger study, exploring the impact of introducing four vaccines in six low-and middle-income countries 15 .…”
Section: African Health Sciences Vol 15 Issue 3 September 2015mentioning
confidence: 99%